Assess the Knowledge, Utilization & Barrier of Non-Utilization Regarding Maternal Health Services - Sonu; Akoijam Mamata Devi; Anu Grover; Deepak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Maternal health services refer to the promotive, preventive, curative and rehabilitative care of mothers. Antenatal care is the care of women during pregnancy the main aim of care is to achieve at the end a healthy baby from healthy mother. Antenatal mothers should be educated regarding regular antenatal checkups, diet, personal hygiene, adequate rest, sleep, exercise, immunization, warning signs of pregnancy and child care. Methods: Descriptive study to assess the knowledge, barriers of non- utilization regarding Maternal Health services. The data was collected using structured knowledge questionnaire and utilization and barriers to non-utilization checklist from 60 postnatal mothers up to 3 months after delivery.Result: The study result showed that women 78.34% had average knowledge and 21.66% had good knowledge regarding maternal health services. Social barriers for non-utilization were family pressure, shyness, poor transportation and illiteracy. Economic barriers for non-utilization were health expenditure perceived as waste, unemployment, low socio economic status and large family size respectively. Cultural barriers for non-utilization were lack of formal education and religious practices respectively, family members disapproved superstition. There was no significant association between knowledge, utilization and barrier on non-utilization of maternal health services and selected demographic variables.Conclusion: The study concluded that postnatal mothers had average knowledge and there is need to create awareness on maternal health services launched by the government of India. Low socioeconomic condition, early marriage and pregnancy, inappropriate antenatal health check-up, and cultural taboos were significant factors affecting the satisfactory utilization of services among mothers. Hence, there is a need to emphasize on utilization and eradicate barriers related to non-utilization of maternal health services